Analisis Preferensi dan Segmentasi Majority Adopter Battery Electric Vehicle di Jabodetabek untuk Strategi Pemasaran Terdiferensiasi - Anggi Pardede; Hasrini Sari (Program Studi Teknik Industri, Fakultas Teknologi Industri, Institut Teknologi Bandung, 2026)
The Indonesian automotive industry is currently undergoing a transition toward electrification, with battery electric vehicles (BEVs) becoming the primary focus of future vehicle development. Although BEV sales have shown an increasing trend in recent years, the national automotive market is still dominated by internal combustion engine (ICE) vehicles and characterized by increasingly intense competition among BEV manufacturers. The expiration of various government incentives in 2025 has also changed market dynamics, meaning that product success is no longer determined solely by price competitiveness or technological innovation, but also by manufacturers’ ability to better understand consumer preferences. Therefore, understanding consumer preferences and market segmentation has become increasingly important in formulating effective marketing strategies. However, limited research has simultaneously integrated BEV attribute preferences and adopter categories within the innovation diffusion framework, creating a gap in understanding how preference structures vary across consumers at similar adoption stages. This limitation may reduce the effectiveness of market segmentation and targeted marketing strategies for BEVs. This study aims to analyze consumer preferences toward BEV attributes, identify market segments based on preference patterns and adopter categories, and formulate relevant marketing strategies for the industry. A quantitative approach was employed using choice-based conjoint analysis (CBCA) and cluster analysis involving 197 respondents in the Greater Jakarta area (Jabodetabek). The analyzed attributes included battery durability, price, safety level, energy consumption, and access to service facilities. The results indicate that battery durability is the most important attribute influencing consumer preferences, followed by access to service facilities, safety, price, and energy consumption. Cluster analysis identified two major segments: Value-Oriented Pragmatists and Risk-Averse Safekeepers. Both segments are dominated by early majority and late majority adopters, indicating that the Indonesian BEV market has entered the mainstream adoption stage. These findings suggest that marketing strategies should focus on risk reduction, tangible benefit demonstration, and differentiated value propositions tailored to the characteristics of each segment.